Diversity of inflorescences in the Boutelouinae subtribe (Poaceae: Chloridoideae: Cynodonteae) - Pilatti, Vanesa (2014)
The Boutelouinae subtribe is comprised of one monophyletic genus, Bouteloua, with 57 species inhabiting the semi-arid regions of the New World. The inflorescences show significant structural variations, which provides an interesting system to examine their morphological evolution and identify characters and processes that may help to understand the group systematics. The structure of inflorescences was studied in 25 species of Bouteloua. All the species covered under this study have truncated polytelic inflorescences. Structural variations in the inflorescence unit among species may be accounted for by: (1) symmetry of the inflorescence unit, (2) total number of long primary branches, (3) total number of spikelets per branch, (4) number of perfect flowers per spikelet, (5) number of rudimentary flowers, and (6) reproductive system. Homogenization and truncation processes account for the diversity of mature inflorescences that exists in Bouteloua. In this work, we discuss the systematic and taxonomic value of the inflorescence in the Boutelouinae subtribe.